Model Matematis Untuk Optimasi Pengendalian Persediaan Bahan Baku Pelet Plastik Pada Lini Industri Produksi PT. Tiplas - Hafid, Ahcmad; Jumali, Muhamad Abdul (Universitas Kadiri, 2026)
This study aims to optimize the inventory control of plastic pellet raw materials in the production line of PT. Tiplas by applying mathematical models consisting of Economic Order Quantity (EOQ), Safety Stock, Reorder Point (ROP), and Total Inventory Cost (TIC). One year of observation shows that raw material usage fluctuates significantly, with notable differences in monthly consumption. Such conditions require the company to implement a more structured and measurable inventory control system to ensure smooth production activities and minimize the risk of stockouts. Analysis of monthly consumption data indicates that the average daily demand reaches 768 units, with a standard deviation of 329.24 units, reflecting a high level of demand uncertainty. Using a probabilistic inventory approach, the study determines the optimal order quantity at 9,601 units, safety stock at 1,880 units, and a reorder point at 11,099 units. The results demonstrate that the applied model provides more efficient inventory control recommendations, reduces total inventory costs, and ensures better readiness of raw material availability to support continuous production operations.